2022
DOI: 10.3389/fmed.2022.792949
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Intake, Hypertension and Cardiometabolic Risk Factors in Children and Adolescents: From Pathophysiology to Clinical Aspects. A Narrative Review

Abstract: Arterial hypertension, dyslipidemia, alterations in glucose metabolism and fatty liver, either alone or in association, are frequently observed in obese children and may seriously jeopardize their health. For obesity to develop, an excessive intake of energy-bearing macronutrients is required; however, ample evidence suggests that fructose may promote the development of obesity and/or metabolic alterations, independently of its energy intake. Fructose consumption is particularly high among children, because th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 187 publications
(190 reference statements)
1
12
0
Order By: Relevance
“…Our meta-analysis is consistent with these findings in that fructose increases heart rate as well as systolic, diastolic, and mean blood pressure. In addition, our results are consistent with studies that revealed that chronic fructose consumption increases systolic and diastolic blood pressure [ 19 , 22 ]. Preclinical studies strongly suggest that the effect of fructose on cardiac function may be further influenced by the dose and duration of fructose intake.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our meta-analysis is consistent with these findings in that fructose increases heart rate as well as systolic, diastolic, and mean blood pressure. In addition, our results are consistent with studies that revealed that chronic fructose consumption increases systolic and diastolic blood pressure [ 19 , 22 ]. Preclinical studies strongly suggest that the effect of fructose on cardiac function may be further influenced by the dose and duration of fructose intake.…”
Section: Discussionsupporting
confidence: 93%
“…According to the United States Department of Agriculture (USDA), fructose intake has continuous increased with an average fructose intake of 37 g/day in 1977 but 49 g/day in 2004 [ 21 ]. The fructose contents of foods and condiments promotes obesity and has an independent effect on hypertension, glucose intolerance and fatty liver diseases [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth noting that, although high levels of fructose in the Western diet are associated with intestinal microbiota disorders, the origin of the fructose is also important: although it is naturally contained in fruit, the amounts are minimal relative to the weight of the fruit itself. Its main sources in the diet are thus fruit juices, as well as nonalcoholic drinks and energy drinks [ 52 ]. Moreover, animal studies have shown that the long-term consumption of high amounts of fructose leads to the development of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Among FODMAPs, fructose is a simple sugar that can be investigated independently, unlike other FODMAPs, because of its unique absorption mechanism in the body and the several metabolic pathways in which it is involved [ 72 ]. Additionally, it can be found in large amounts in fruits, honey, and syrups and is often added to several processed foods in the Western diet as sucrose or high fructose corn syrup, resulting in its consistent consumption over the past few decades [ 73 ].…”
Section: Which Foods and Food Patterns Can Cause Intolerance?mentioning
confidence: 99%